1997
DOI: 10.1097/00000539-199710000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Attenuates Ischemia-Reperfusion Injury in the Isolated Rat Heart

Abstract: It is important to protect the heart from injury by ischemia and reperfusion. The current study demonstrates that in the isolated rat heart, propofol attenuates mechanical, biochemical, and histological changes causes by ischemia and reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…2,17 Based on work from our lab and others using both simulated models of ischemia reperfusion and studies in patients, [18][19][20][21][22][23][24][25] we postulated that propofol confers cardioprotection when a target range of 4.5-8.9 lg Á mL -1 (25 to 50 mM) is achieved.…”
Section: Résumémentioning
confidence: 99%
“…2,17 Based on work from our lab and others using both simulated models of ischemia reperfusion and studies in patients, [18][19][20][21][22][23][24][25] we postulated that propofol confers cardioprotection when a target range of 4.5-8.9 lg Á mL -1 (25 to 50 mM) is achieved.…”
Section: Résumémentioning
confidence: 99%
“…Kokita et al reported that propofol preserved the high-energy phosphates ATP and PCr in their Langendorff rat heart model of hydrogen peroxide-induced myocardial damage. 16 Although some have shown propofol to improve contractility following reperfusion, [13][14][15][16][17] others have shown no effects. 18,19 Reduction of myocardial necrosis by propo-982 CANADIAN JOURNAL OF ANESTHESIA FIGURE Ejection fraction (EF; mean ± SEM) normalized by the baseline (B) for both groups at each time-point (O = occlusion; R = reperfusion; D3 = day three follow-up; D10 = day ten followup).…”
Section: Infarct Ratiomentioning
confidence: 99%
“…15,18 Also, these propofol studies involved induction and/or general anesthesia with different anesthetics, followed by a bolus or infusion of propofol at some specific limited time-point. 13,[15][16][17][18][19] This leads to further confounding variables within the studies as the two different anesthetics are now integrated, making it extremely difficult to interpret the effects of propofol alone.…”
Section: Infarct Ratiomentioning
confidence: 99%
See 2 more Smart Citations